Perancangan dan Pembuatan Data Warehouse dan Business Intelligence pada Market Research Motorcycle Honda MPM Motor - Erriv Septianfan Budi; Leo Willyanto Santoso; Lily Puspa Dewi (Jurnal Infra, 2019)
Honda MPM (Mitra Pinasthika Mulia) Distributor have a market research system that only covers internal matters such as sales results, and Honda MPM Distributors also use government data in making decisions. However, in collecting and analyzing government data, Honda MPM Distributor company is done by typing government data on the Microsoft Excel program manually and table reporting that is not connected with sales data. This led to the slow pace of the market research process and wasted considerable time coupled with the large number of areas divided between villages and cities.Therefore, the data warehouse as business intelligence is needed by Honda MPM Motor companies in accelerating company data management process and as a tool to help create reports that could simplify their analysis on market research.Data collected in the data warehouse is correct and complete. The resulting report helps facilitate the provision of needed division head information for market research in a city / regency concerning economic GRDP (Gross Regional Domestic Product) crops, livestock, services, population development and motor population, and motorized sales details (buyer’s gender, motor type purchased, buyer's job) through the Power BI application. But, the application can continue to grow with increasing data obtained from the government. Based on the results of the questionnaire conducted 80% both 20% is very good for the convenience provided by this reporting application as an effort to help market analysis and 60% good 40% is very good for the overall reporting program.